Bryophyte Diversity in Mount Prau, Blumah Village, Central Java - Lianah, Lianah; Kusumarini, Niken; Rochmah, Fitriana; Orsida, Fadla; Mukhlisi, Mukhlisi; Ahmad, Milya Ulfa; Nadhifah, Ainun (Jurnal Biodjati, 2021)
Bryophytes areÂ aÂ major component of the ecosystem in Indonesia. Due to their sensitiveness, the abundance and diversity of bryophytes in an ecosystem are influenced byÂ environmental conditions.Â This study aimedÂ to determine the diversity of bryophytesÂ based on ecological parameters in the village of Blumah Kecaman Plantungan, Kendal Regency which is directly adjacent to the Mount Prau protected forest, Central Java. The data collection method used wasÂ the exploratory method and the descriptive exploratory method with survey techniques. Observation was carried out by exploring an area of Â 3 kilometers, every 1 km distance.Â An observation station wasÂ made consisting of station 1 Jiwan hamlet, station 2 Garung, and station 3 at Cengkek and Gondan springs. The specimensÂ were identified based on taxonomic literature. Each speciesÂ was collected as a specimen for further identification in the laboratory. Abiotic environment parameters such asÂ temperature, humidity, altitude, light intensity, pH and slopeÂ were observed.Â The results showed that Blumah village still has high plant diversity, especially bryophytes. The more humid, the higher the place, the lower the temperature andÂ lightÂ intensity, the more species diversity. Based on the identification results, 21 species were recorded,Â which includes 15 species of mosses, 4 species of liverworts, and 2 species of hornworts. The index value of bryophyteÂ species diversity wasÂ in the medium category, and the index value of species richness and species dominance wereÂ at low levels.